Factors contributing to appropriateness of utilisation among adult patients attending Emergency Department Hospital Kuala Kubu Bharu 2017 - Ng, Anthony Tyng Ruey (2017)
Introduction: Emergency and non- emergency utilisation at hospital emergency department is a common occurrence around the world as well in Malaysia. In Selangor, there had been a general increase in the numbers of patients seeking treatment at the emergency department. Such utilisation if inappropriate give rise to overcrowding, long waiting times and unnecessary usage of healthcare resources.